Strategic Management for Restaurant Business (Case Study: Kedai PAPA LIEM Restaurant) - Ihsan, Muhammad; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract. This research devoted to evaluate the business strategy that currently being used by Kedai Papa Liem, a small restaurant that serve for all day dining occasion from breakfast until dinner. The restaurant purposely located near Setra Duta Real Estate main gate to scoop up all residents that lived inside Setra Duta Real Estate that said to be Kedai Papa Liem’s main target market. Kedai Papa Liem first opening was in late-November 2013. They received a good response from the market. But since mid-January 2014 Kedai Papa Liem faces some difficulty to growth. The market started to saturated along with many new restaurant that opened around Pasteur road. Moreover those new restaurants are popular in Jakarta, so it attract many people included Setra Duta Resident which is Kedai Papa Liem’s main customer to try them. This condition would disturb their plan to hold a Grand Opening in early February 2014, to celebrate Chinese New Year.The main problem they encountered was from internal factor, which is bad human resources management and business process. The other factor was because of the competition of Restaurant Industry in Bandung that keep tightens. On other hand she has a chance to broaden the market reach of her restaurant. Seeing the growth opportunities that available to grow her business, she start to think whether her restaurant able to be developed and how to do it.To start the research, first thing to do was analyzed internal and external factor that influenced Kedai Papa Liem’s performance. The result would be used as the basis for EFAS and IFAS calculation to determine what directional strategy that suitable for corporate level. After that Business Strategy determined through Porter Competitive analysis with cost production and market size as the consideration. Last, TOWS matrix analysis would be conducted to determine functional strategies that used for each division in Kedai Papa Liem.The results were showing that Kedai Papa Liem could develop their business by using Growth Strategy because both result of IFAS and EFAS calculations showing positive number. On other hand, Business Strategy that suitable for Kedai Papa Liem was Integrated Competitive Strategy. This strategy would be used to win the competition among other restaurant so their sales performance will be To support their development plan in expansion, they should have more market share in Bandung’s Restaurant Industry by provide more variant in product, with more affordable price than their competitors.Keyword: Strategic Management, Restaurant.